The Role of Epstein-Barr virus LMP1 Gene Expression in Chromosome Rearrangements in Nasopharyngeal Carcinoma - Mohd Aminudin, Mustapha; Sai Peng, Sim (Universiti Malaysia Sarawak, 2025)
Nasopharyngeal carcinoma (NPC) is strongly associated with Epstein-Barr virus (EBV) infection, particularly the expression of the viral oncogene Latent Membrane Protein 1 (LMP1). LMP1 is known to induce oxidative stress, apoptosis, and genomic instability, which may contribute to chromosome rearrangements—a hallmark of cancer progression. However, the precise mechanisms by which LMP1 expression leads to chromosomal breaks and rearrangements, particularly within the AF9 gene, remain unclear. This study aimed to establish a transient LMP1 gene expression system and investigate its effects on oxidative stress, apoptosis, and chromosome breaks, particularly within the AF9 gene, while also evaluating the role of MAR/SAR sequences in mediating these breaks. LMP1 gene constructs in pTracer and pcDNA forms were transfected into a normal nasopharyngeal cell line to assess ROS levels and LMP1-induced apoptosis through Caspase activity measurement. Inverse PCR (IPCR) was utilized to detect chromosomal breakage in scaffold-attachment region (SAR) and non-SAR regions of the AF9 gene in LMP1-expressing cells. The results showed no significant differences in ROS production between pTracer-LMP1, pcDNA-LMP1, and their combination compared to the vector control. However, pcDNA-LMP1 exhibited significantly higher Caspase activity than the pcDNA vector control. Furthermore, LMP1 expression showed significant differences in chromosome breaks within the SAR compared to the control. Statistical analyses revealed a significant association between LMP1 transfections and increased chromosome breaks in the SAR, suggesting a higher risk of chromosomal instability. Conversely, LMP1 transfections did not significantly affect chromosome breaks in the non-SAR, indicating a region-specific effect. These findings suggest that LMP1 expression may trigger oxidative stress-mediated apoptosis, which contributes to chromosome rearrangements and plays a role in the pathogenesis of nasopharyngeal carcinoma (NPC). Keywords: Nasopharyngeal carcinoma, Epstein–Barr virus, latent membrane protein 1, reactive oxygen species, caspase activity scaffold-attachment region